Lead‐Free Dual‐Phase Halide Perovskites for Preconditioned Conducting‐Bridge Memory. Issue 41 (18th September 2020) - Han, Ji Su; Le, Quyet Van; Kim, Hyojung; Lee, Yoon Jung; Lee, Da Eun; Im, In Hyuk; Lee, Min Kyung; Kim, Seung Ju; Kim, Jaehyun; Kwak, Kyung Ju; Choi, Min‐Ju; Lee, Sol A; et al.
Abstract: Organometallic and all‐inorganic halide perovskites (HPs) have recently emerged as promising candidate materials for resistive switching (RS) nonvolatile memory due to their current–voltage hysteresis caused by fast ion migration. Lead‐free and all‐inorganic HPs have been researched for non‐toxic and environmentally friendly RS memory devices. However, only HP‐based devices with electrochemically active top electrode (TE) exhibit ultra‐low operating voltages and high on/off ratio RS properties. The active TE easily reacts to halide ions in HP films, and the devices have a low device durability. Herein, RS memory devices based on an air‐stable lead‐free all‐inorganic dual‐phase HP (AgBi2 I7 ‐Cs3 Bi2 I9 ) are successfully fabricated with inert metal electrodes. The devices with Au TE show filamentary RS behavior by conducting‐bridge involving Ag cations in HPs with ultra‐low operating voltages (<0.15 V), high on/off ratio (>10 7 ), multilevel data storage, and long retention times (>5 × 10 4 s). The use of a closed‐loop pulse switching method improves reversible RS properties up to 10 3 cycles with high on/off ratio above 10 6 . With an extremely small bending radius of 1 mm, the devices are operable with reasonable RS characteristics. This work provides a promising material strategy for lead‐free all‐inorganic HP‐based nonvolatile memory devices for practical applications. Abstract : Preconditioned resistive switching (RS) memory devices with inert metal electrodes are successfully fabricated using lead‐free dual‐phase halide perovskites (HPs). The devices show filamentary RS behaviors with ultra‐low operating voltages, high on/off ratio, multilevel data storage, long retention times, and high endurance. High flexibility and air‐stability provide a promising material strategy for the design of lead‐free all‐inorganic HP‐based nonvolatile memory devices.